دور قواعد الحوكمة في تحسين قدرة المراجع على اكتشاف الغش في القوائم المالية "دراسة ميدانية على الشركات المدرجة في هيئة الأوراق المالية السورية" - العربيد, عصام فهد; العثمان, محمد نادر; عاصي, أحمد عيسى (Latakia University Journal - Economic and Legal Sciences Series, 2015)
تهدف هذه الدراسة إلى التعرف على الدور الذي تقوم به قواعد حوكمة الشركات المساهمة السورية, في تقدير المراجع الخارجي لاحتمال الغش في القوائم المالية؟ وما هو نوع هذا الأثر؟ وأي القواعد أكثر تأثيراً؟ وفي سبيل ذلك فقد استعرض الباحث مفهوم حوكمة الشركات, ومفهوم الغش في القوائم المالية, ومسؤولية المراجع عن تقديره واكتشافه, ومن ثم العلاقة التي تربط بين قواعد حوكمة الشركات واكتشاف الغش, وقد عرض الباحث بعض الدراسات السابقة التي تناولت العلاقة بين حوكمة الشركات والغش في القوائم المالية, ولتحقيق هدف البحث المتمثل بمعرفة الدور الذي تلعبه حوكمة الشركات في تقدير المراجع الخارجي لاحتمال الغش في القوائم المالية, تم تصميم استمارة استبانة تشتمل عدة حالات تم توظيفها للتعامل مع كل فرضية من فرضيات البحث التي تم استخلاصها من خلال مراجعة الدراسات السابقة، وقد بلغت نسبة الاستبانات المجاب عليها 70.97% حيث أظهرت نتائج الدراسة وجود أثر إيجابي لحوكمة الشركات بشكل عام وأثار مختلفة لكل قاعدة من قواعد الحوكمة بشكل مستقل. واختتمت الدراسة ببعض التوصيات حيث أوصى الباحث بتفعيل الحوكمة في الشركات المساهمة السورية من خلال التزام جميع الشركات المدرجة في هيئة الأوراق والأسواق المالية, بتطبيق قواعد الحوكمة بشكل جيد لما لهذا التطبيق من أثار إيجابية على تحسين جودة القوائم المالية وبالتالي قدرة المراجع الخارجي على تقدير احتمال الغش. This study aims to identify the role played by the rules of corporate governance contribute to the Syrian, in the estimation of the external auditor for the possibility of fraud in the financial statements, and what kind of impact this and any rules more effective. For that it has reviewed the researcher concept of corporate governance, and the concept of fraud in the financial statements, and the responsibility of references appreciation and discovery, according to some international standards and the U.S., has introduced a researcher some previous studies on the relationship between corporate governance and fraud in the financial statements , and to achieve the aim of the research objective knowledge of the role played by corporate governance in the estimation of the external auditor for the possibility of fraud in the financial statements , is designed to form questionnaire includes several cases have been employed to deal with all the hypothesis of the research hypotheses which have been drawn by reviewing previous studies, where the percentage of questionnaires, missed calls 70.97 % showed results study the existence of a positive impact of corporate governance in general and raised the base is different for each of the governance rules independently. The study concludes with some recommendations where the researcher recommended activating governance in companies contributing to Syria through the commitment of all companies listed on the stock and financial markets, the application of the rules of governance well to this application of a positive impact on improving the quality of financial statements, and thus the ability of the external auditor to assess the likelihood of fraud.